Fisiability Analysis of Honey Bee Cultivation in Baruga Village, Banggae District, Majene Regency - Widyanti Utami; Muhammad Sarif; Muhammad Ihsan (Universitas Andi Djemma Palopo, 2023)
Honey bee farming has long been known by the public. This business requires land, capital, labor, knowledge and skills as well as good management. This study aims to determine the amount of income and feasibility in one production period. This research was conducted in Baruga Village, Sendana District, Majene Regency. Collecting data using direct interview techniques with farmers. Data analysis used in this research is descriptive analysis, income and business feasibility. The results showed that the income from the Trigona sp honey bee cultivation business in Baruga Village, Sendana District, Majene Regency was Rp. 29,896,500 / production period. The Revenue of Cost Ratio (R/C) value is 2.44, this indicates that the farmer's honey bee cultivation business in Baruga Village, SendanaÂ District, Majene Regency is feasible.